Please help me with this is so confusing
![Please help me with this is so confusing class=](https://us-static.z-dn.net/files/d2d/31b2bd58b10e0d9ebded931c837ac60a.png)
Answer:
The expression for the height of the solid is:
[tex]\displaystyle h = x^2+x-9[/tex]
Step-by-step explanation:
Recall that the volume of a rectangular solid is given by:
[tex]\displaystyle V = \ell wh[/tex]
Where l is the length, w is the width, and h is the height.
We know that the volume is given by the polynomial:
[tex]\displaystyle V = 3x^4-3x^3-33x^2+54x[/tex]
And that the length and width are given by, respectively:
[tex]\displaystyle \ell = 3x \text{ and } w =x-2[/tex]
Substitute:
[tex]\displaystyle 3x^4-3x^3-33x^2+54x=(3x)(x-2)h[/tex]
We can solve for h. First, divide both sides by 3x:
[tex]\displaystyle \frac{3x^4-3x^3-33x^2+54x}{3x}=(x-2)h[/tex]
Divide each term:
[tex]\displaystyle x^3-x^2-11x+18=(x-2)h[/tex]
To solve for h, divide both sides by (x - 2):
[tex]\displaystyle h = \frac{x^3-x^2-11x+18}{x-2}[/tex]
Since this is a polynomial divided by a binomial in the form of (x - a), we can use synthetic division, where a = 2. This is shown below. Therefore, the expression for the height of the solid is:
[tex]\displaystyle h = x^2+x-9[/tex]